The The Influence Of Training On Increasing Farmers' Knowledge In Healthy Agriculture Based On Agricultural And Health Education In Lebojaya Village, Konda District: Training On Increasing Farmers' Knowledge - Tasnim Tasnim; Jastria Pusmarani; Ari Tjahyadi Rafiuddin (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2022)
Objectives: This study aims to analyze the effect of training using lecture and practice methods with power point presentation media and leaflets on farmers' knowledge in healthy agro-tourism based on agricultural and health education in Lebojaya Village, Konda District, Southeast Sulawesi. Methods: This study used a quantitative method with a quasi-experimental approach with a one group pretest-posttest design. A total of 16 farmers were trained using lecture and practice methods and power point presentation media and leaflets. Data analysis used the Wilcoxon sign rank test. Training material on balanced nutrition and nutritional content and the benefits of corn and carrots for body health. Results: The results of this study indicate that there is an increase in farmers' knowledge about balanced nutrition and nutritional content and the benefits of corn and carrots for health. After the training, almost all of the participants' knowledge increased. Where participants who scored above 70 after the training increased by 25%, from 62.5% to 87.5%. The test results showed that there was a significant difference between farmers' knowledge before and after training (p=0.006 <0.05). Conclusion: Nutrition science training using lecture and practice methods, as well as the use of media power point presentations and leaflets have a significant effect on increasing farmers' knowledge in healthy agro-tourism locations based on agricultural and health education in Lebojaya Village, Konda District. Due to the combination of lecture media and practice as well as the use of media, participants gain knowledge through various senses namely the senses of hearing, seeing and experiencing.